TINDAK TUTUR ILOKUSI DIREKTIF DALAM DEBATCAWAPRES REPUBLIK INDONESIA TAHUN 2024 DALAM PERSPEKTIF TEORI PRAGMATIK - Anis Rahmadhani; Farida Yufarlina Rosita; Berlian Pancarrani (University of Brawijaya, 2024)
This research is undermined by the observance of directive illusions in the presidency debate of the Republic of Indonesia in 2024. The aim of the study was to describe the observance of directive illusions in the presidency debate of the Republic of Indonesia in 2024 and to explain how speakers use language to the purpose of action and how the speaker partners conclude the meaning intended to shape what is said. This research method uses descriptive qualitative methods to describe data compliance with directive illusions in the presidential debate of the Republic of Indonesia in 2024. The theory used in this study is the pragmatic theory, where pragmatics is the linguistics that study the meaning of the speaker. The results of the research show that the fulfillment of the illusion of the directive that emerges is questions and demands. It shows variations in the use of obedience to directive illusions, including orders, requests, suggestions, and prohibitions, used by the vice president to influence the views and actions of voters. In addition, the rhetorical strategy used in the debate also affects the effectiveness of following the illusion of directives in achieving the desired communicative objectives. Implications of this research are a better understanding of the use of language in political contexts and the importance of pragmatic analysis in understanding verbal interaction in the political arena.